Administration of English Language Programme in Nigerian Higher Institutions: Problem, Issues and Suggestion - Ogunode Niyi Jacob (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2020)
The article discussed the problems facing the administration of English language programme in the Nigerian higher institutions. Secondary data was used to support the points raised in the article. The secondary data were sourced from print material and online publication by recognized institutions and individual author. The problems facing the administration of English language programme in Nigerian higher institution include; inadequate funding, inadequate English language lecturers, inadequate English language laboratories, poor research in English language programme, brain-drain, strike actions, poor capacity development of English language programme lecturers and institutional corruption. For effective administration of English language programme in the Nigerian higher institutions, the paper hereby recommends: that the government should increase the funding of English language programme, employment of more English language lecturers, provision of adequate infrastructural facilities, implementation of agreement with unions, effective staff development programme, effective motivation policy to prevent brain-drain and fight all the institutional corruption in the higher institutions